Effects of culture and age on attitudes to mobile technology - Abd Malik, Sofianiza (2012)
Use of mobile technology is becoming a necessary part of everyday life – and not just in the developed world. Exclusion – for any reason – is a serious disadvantage and one group who face exclusion is older people. This research looked into reasons why older people in a developed country (the UK) and a developing country (Malaysia) might be excluded. The project first tackled the problem of how to elicit information from these people, applying talking methods, with and without personas. The results were probed more deeply and verified through a card-sorting study and a questionnaire. A number of problems common among all the participants were found. In addition there were some culture-related differences between the countries, although they were small.